PROSES PENGKELATAN MINYAK CENGKEH DENGAN ASAM SITRAT - Silviana, Silviana (METANA, 2007)
Abstract   Clove leaf oil is essential oil produced by distillation of clove leaf. The oil is still dark color and low eugenol content, generally. It was caused by Fe content in the oil, so the oil has dark color. Furthermore, it needs to improve the value of clove leaf oil through chelating process with citric acid. The objective of research is to obtain the significant variable for content and volum response. The research conducts with initial Fe content, chelating process, and final analysis of Fe content. Analysis of Fe content uses Spectrofotometry. The research uses design of experiment: factorial design 24 with variables: citric acid concentration (1- 2%b), temperature (50oC – 70oC), time (l - 2 hours) and stirring speed (300-600 rpm). Data treatment obtained using Design Expert software. The result shows that temperature and time are significant variable for decreasing Fe content. Decreasing of Fe content from initial content 22,98mg/L down to l,86 - 2l,26mg/L. Regresion model obtained is Eugenol =74,45 + 0,10325 temperature. However, absorbent concentration and stirring speed variables have significant influent for decreasing volume. The regresion model obtained is Fe content = 34,6075-(0,54775T)-29,0551+0,548Tt, where T  is temperature and t is time of chelating process.   Key word: clove leaf oi;  chelaling;  citric acid; Fe  content